2006
DOI: 10.1055/s-2006-949972
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grape consumption on plasma and erythrocyte antioxidant parameters in elderly subjects

Abstract: Aim:To investigate the effects of ingesting Fructus vitis minuta (black grape) on plasma and erythrocyte antioxidant parameters in elderly subjects. Materials and methods:Thirteen subjects (mean age 74.67 ± 0.58) participated in the study. They consumed 1 g/kg body weight per day of dried black Maraş grapes for 1 month. Before and after these periods, fasting blood samples were obtained, and oxidant (as MDA) and antioxidant (as SOD) parameters were studied in erythrocytes. Also, plasma samples were obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
3
5
0
Order By: Relevance
“…group. This result conform the result of [37] who observed that phytochemical from plant-rich diets, including garlic, provide important additional protection against oxidant damage. Garlic extract supplementation improves blood lipid profile, strengthens blood antioxidant potential, and also leads to a decrease in the level of oxidation product (MDA) in the blood samples, which demonstrates reduced oxidation reactions in the body [38,39].…”
Section: Discussionsupporting
confidence: 90%
“…group. This result conform the result of [37] who observed that phytochemical from plant-rich diets, including garlic, provide important additional protection against oxidant damage. Garlic extract supplementation improves blood lipid profile, strengthens blood antioxidant potential, and also leads to a decrease in the level of oxidation product (MDA) in the blood samples, which demonstrates reduced oxidation reactions in the body [38,39].…”
Section: Discussionsupporting
confidence: 90%
“…GSkM contains more catechin derivatives with gallyl moiety. The flavan-3-ol content and its correspondence with radical scavenging potency in the grape seed extracts were in accordance with the findings of other authors (27,28). However, Bozan et al (10) asserted that the higher antiradical activity of the extracts with lower C content may result from other flavonoid components of the extracts.…”
Section: Discussionsupporting
confidence: 88%
“…[3][4][5][6] Various garlic preparations and components have also been shown to have antioxidant activity, including the ability to lower reactive oxygen species in vivo. [7][8][9] We recently reported that using a model of DOX-induced heart damage in rats, pretreatment with aged garlic extract (AGE), a strong antioxidant, offered protection against DOXinduced myocardial cell damage. 4 The present study was undertaken to investigate how AGE could protect the rat heart against DOX-induced cardiotoxicity and whether this interaction could be at the expense of antitumor activity of DOX.…”
Section: Introductionmentioning
confidence: 99%